"A very hot story": Eroticism in Flannery O'Connor's "Good Country People". - GOURDOUX, EVA (Flannery O'Connor Review, 2024)
The article presents a thematic and stylistic analysis of the short story "Good Country People" by Flannery O'Connor. Topics discussed include the depiction of eroticism in the short story, the mind against body conflict of the character Joy who named herself Hulga, and the Joy-Hulga character's navigation between desire and innocence.